2019
DOI: 10.3233/blc-180199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a European Bladder Cancer Predictive Model for Non-Muscle Invasive Bladder Cancer in an Australian Cohort

Abstract: Background and Objectives: To validate the European Organization for Research and Treatment of Cancer (EORTC) model using an Australian cohort and to identify variables within our cohort that may predict non-muscle invasive bladder cancer (NMIBC) recurrence and progression. Methods: A retrospective chart review of patients undergoing transurethral resection of bladder tumour (TURBT) at a single academic institution between 1995 and 2015 was performed (n = 366). Only patients with available TURBT pathology havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 included studies, five included only Ta NMIBC patients [12–16], and 26 studies included only T1 NMIBC patients [17–42]. The other 41 studies included both Ta and T1 patients [43–83].…”
Section: Resultsmentioning
confidence: 99%